Detecting the effect of methyl viologen on photosystem ii of euglena by O-J-I-P chlorophyll fluorescence transients - Eeswaran, R.; Raveendra, S.A.S.T.; Beneragama, C.K. (University of Peradeniya, 2013)
The measurement of direct chlorophyll a fluorescence in photosystem II (PSII) and the JIP test based O-J-I-P polyphasic transient analysis is becoming increasingly popular among the techniques suitable for accessing effects of stress conditions on the photosynthetic apparatus. In the present study, the well known effects of Methyl Viologen (MV) which is commonly known as “Paraquat” on the photosynthetic apparatus were probed by the JIP test in Euglena, a unicellular autotrophic organism which has a chlorophyll a/b antenna system as it is typical of higher plants. The cells were exposed to a series of MV doses as control, 0.1, 0.2, 1 and 2 mmol and, immediately after the exposure; the chlorophyll fluorescence was measured using AquaPen AP-C 100 fluorometer. The resultant O-J-I-P transients were analyzed according to JIP-test and several functional and structural parameters were derived to explain the PSII behavior.